ANALISIS FINANSIAL DIVERSIFIKASI PRODUK KELAPA MENJADI VCO (Virgin Coconut Oil) DENGAN METODE EMULSI - Imaculata Fatima (AGRICA, 2008)
Coconut plant is a plant that grows in a tropical area. It dominates growing in the coastal area. Ende Regency is a part of the district, located in East Nusa Tenggara Provence particularly in Flores island. The plan is one of the commodities in Ende that support it increase the income of the people generally. However, coconut is relatively low. For instance, one fruit is five hundred or a thousand rupiah. In reality, each plant of coconut can produce 25-30 fruits every month (APCC, 2004). Most of the coconut plants in Ende is a kind of local coconut which is known "Kelapa Dalam Lokal". This kind of commodity contains high oil quality which may be treated to produce more oil. Traditionally, farmers usually produce coconut oil which can improve their home income. This oil production is well known in Ende regency as "klentik oil or tandusan oil". Most people and farmers say that oil production can not give enough benefits or profits for supporting their home economic. For this reason, it is very important to change the way of how to treat coconut fruits in order to give more quality of the coconut oil. This new way is recognized as the emulsion method. Its actually is a new technology to process the coconut fruit to become virgin coconut oil (VCO). This analysis is conducted to find out the validity of the production and to know the profits of the production in regards to improving the income of the farmer. Financial analysis includes the analysis of validity in interpreneuring (R/C ratio), the impact price, and impact focus of production. Producing the virgin coconut oil has run at Faculty of Agriculture, Flores University on semester IV, period 2007- 2008. The validity analysis indicates that the R/C ratio peaks 2,69. It shows that this product is suitable to be carried on. The treatment of coconut oil and klentik oil. The price of 80 coconut fruits can produce 7.500 ml VCO and 1.500 ml klentik oil. The price of the VCO is Rp. 46,93,- per ml while production impact is 1.700 ml. In contrast to the price of kentik oil is Rp. 174,67,- per ml while its production impact is 2.620 ml. Thus, from the financial aspect, diversification of coconut to become virgin coconut oil and klentik oil simultaneously with emulsion method is appropriate to be conducted by farmers of coconut in order to improve their production the future time.